Strategi Komunikasi Politik Calon Kepala Desa (Studi Komunikasi Politik dalam Pemilihan Kepala Desa di Desa Bendosari Kecamatan Kras Kabupaten Kediri) - Nathan, Arik (Jurnal Administrasi Publik, 2014)
Abstrak: The Political Communication Strategy for the Head Village (A Study of the Political Communication in a Heas Village Election in Desa Bendosari Kecamatan Kras Kabupaten Kediri). The political communication strategy is usually done in any election either in the level of national, province, regency, or village. In the village level, the election is done to select the head of the village. In order to get as many as vote, the candidates have to implement the political communication strategy to the voters or the villagers; it is including the candidates of head of the Bendosari village. In the election. The purpose of the study was describing and analyzing the political communication strategies as well as supporting factors and the obstacles for the candidates in the head village election in Bendosari village, Kras, Kediri. The result of the study showed that the political communication strategy used by the head village candidates were including firstly creating a persuasive message by stating the development, services, and welfare planning for the society. Secondly, the candidates used several media, they are billboards and mouth by mouth information. Thirdly, the candidates were also willing to do home visiting (door to door) and held and open house to welcome the people who come to their house. Regarding the supporting factors and the obstacles, the former was considered as the elements that help them during the political communication strategy, such as money, well-known figures, and a good background. Keywords: head village, political communicationAbstrak: Strategi Komunikasi Politik Calon Kepala Desa (Studi Komunikasi Politik dalam Pemilihan Kepala Desa di Desa Bendosari Kecamatan Kras Kabupaten Kediri). Strategi komunikasi politik umumnya digunakan pada pemilihan umum tingkat negara, provinsi, kota/kabupaten bahkan desa. Dimana dalam tingkat desa diselenggarakan Pemilihan kepala desa, dimana untuk memenangkan sebuah pemilu diperlukan strategi komunikasi politik. Tidak terkecuali pemilihan kepala desa di Desa Bendosari. Sehubungan dengan hal tersebut penelitian ini bertujuan untuk mendeskripsikan dan menganalisis strategi komunikasi politik, dan faktor pendukung dan penghambat calon kepala desa dalam Pilkades di Desa Bendosari Kecamatan Kras Kabupaten Kediri. Hasil penelitian ini menunjukkan bahwa strategi komunikasi politik yang dilakukan oleh calon Kepala Desa Bendosari yaitu pertama menyusun pesan persuasif yaitu dengan menyampaikan pesan pembangunan, pelayanan dan kesejahteraan masyarakat, kedua memilah dan memilih media yaitu dengan menggunakan media baliho dan melalui mulut ke mulut. Ketiga bersedia membuka diri yaitu dengan melakukan kunjungan ke rumah-rumah (door to door) dan menyediakan waktu dan rumahnya untuk menjamu masyarakat yang berkunjung. Tidak terlepas dari adanya faktor pendukung dan penghambat di dalam perjalanannya. Kata kunci: kepala desa, komunikasi politik